Making researchers responsible: attributions of responsibility and ambiguous notions of culture in research codes of conduct - Valkenburg, Govert (BMC Med Ethics, 2020)
BACKGROUND: Research codes of conduct offer guidance to researchers with respect to which values should be realized in research practices, how these values are to be realized, and what the respective responsibilities of the individual and the institution are in this. However, the question of how the responsibilities are to be divided between the individual and the institution has hitherto received little attention. We therefore performed an analysis of research codes of conduct to investigate how responsibilities are positioned as individual or institutional, and how the boundary between the two is drawn. METHOD: We selected 12 institutional, national and international codes of conduct that apply to medical research in the Netherlands and subjected them to a close-reading content analysis. We first identified the dominant themes and then investigated how responsibility is attributed to individuals and institutions. RESULTS: We observed that the attribution of responsibility to either the individual or the institution is often not entirely clear, and that the notion of culture emerges as a residual category for such attributions. We see this notion of responsible research cultures as important; it is something that mediates between the individual level and the institutional level. However, at the same time it largely lacks substantiation. CONCLUSIONS: While many attributions of individual and institutional responsibility are clear, the exact boundary between the two is often problematic. We suggest two possible avenues for improving codes of conduct: either to clearly attribute responsibilities to individuals or institutions and depend less on the notion of culture, or to make culture a more explicit concern and articulate what it is and how a good culture might be fostered.